Osteochondral Autologous Transplantation Versus Dorsal Closing Wedge Metatarsal Osteotomy for the Treatment of Freiberg Infraction in Athletes: A Randomized Controlled Study With 3-Year Follow-up. Issue 10 (August 2019) - Georgiannos, Dimitrios; Tsikopoulos, Kostas; Kitridis, Dimitrios; Givisis, Panagiotis; Bisbinas, Ilias
Background: Dorsiflexion closing wedge metatarsal osteotomy (DCWMO) has been considered the traditional treatment of Freiberg disease. Several case reports presented osteochondral autologous transplantation (OAT) as an alternative treatment. Purpose/Hypothesis: The purpose was to compare the results of DCWMO versus OAT for the treatment of Freiberg infraction in an athletic population. It was hypothesized that OAT was superior to DCWMO regarding functional outcomes, pain, and the time that the athletes returned to training and to previous sport level. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: Between 2008 and 2013, 27 consecutive patients with Freiberg disease were randomly assigned to either the DCWMO group (14 patients) or the OAT group (13 patients). The primary outcomes collected were as follows: postoperative complications, range of motion of the metatarsophalangeal joint, length of the metatarsal, function of the foot (measured with the American Orthopaedic Foot and Ankle Society–lesser metatarsophalangeal-interphalangeal [AOFAS-LMI] score), and pain (assessed with the visual analog scale–foot and ankle score). Results: Mean follow-up was 46 months (range, 36-60 months). The mean ± SD AOFAS-LMI score in the DCWMO group was 63.4 ± 14.4 preoperatively, 81.8 ± 6.6 at 1 year postoperatively, and 84.4 ± 5.6 at 3 years postoperatively, while in the OAT group, it was 62.8 ± 14, 89.9 ± 7.1, and 92 ± 6.9, respectively ( P < .001). The differences in the AOFAS-LMI scores favoring the OAT group at 1 and 3 years reached statistical but not clinical significance. The mean visual analog scale–foot and ankle score was improved significantly from 48.1 ± 11.5 to 91.8 ± 9.5 in the DCWMO group and from 49.9 ± 10.9 to 95.4 ± 4.4 in the OAT group. There was a shortening of the metatarsals by a mean 1.9 ± 0.5 mm in the DCWMO group, as opposed to a metatarsal lengthening of 0.2 ± 0.1 mm in the OAT group. In the OAT group, patients were able to start training at 6 ± 1 weeks ( P < .001) and return to full sport action at 10 ± 2.5 weeks ( P < .05), while in the DCWMO group, the time was 8 ± 1.5 and 13 ± 2.5 weeks, respectively. Conclusion: The authors concluded that OAT is equal to DCWMO. Acceptable clinical results were reported, as well as very low morbidity and early return to sport activities. That makes the OAT procedure a safe, effective, and optimal treatment for an athletic population experiencing Freiberg infraction.